Gluing layer and preparation method thereof, diaphragm, electrode, lithium ion battery and preparation method thereof, and electric equipment

By applying a specially made glue coating layer on the separator and electrode of the lithium-ion battery, the problem of uneven breathability in the prior art is solved, the capacity retention rate and ion transmission efficiency of the battery are improved, and the battery performance is improved.

CN119852304APending Publication Date: 2025-04-18BYD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410141227.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-01-31
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The current PVDF glue coating technology in water system has a large increase in breathability and uneven breathability, which affects the capacity retention rate and ion transmission rate of lithium-ion batteries.

Method used

A glue coating layer is provided, which has pores and a breathability of 10s/100ml to 35s/100ml. On a plane perpendicular to the thickness direction of the glue coating layer, the breathability deviation is not greater than 2s/100ml. The glue coating layer consists of glue powder, dispersant and binder, and is prepared by specific mixing and molding treatment methods, suitable for the separator and electrode of lithium-ion batteries.

Benefits of technology

It improves the battery capacity retention rate and lithium ion transmission efficiency, improves battery performance, and has low breathability, small breathability deviation, strong applicability, and is easy to produce on a large scale.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852304A_ABST
    Figure CN119852304A_ABST
Patent Text Reader

Abstract

The invention provides a gluing layer which is characterized in that pores exist in the gluing layer, and the air permeability of the gluing layer is 10 s / 100 ml to 35 s / 100 ml; on a plane perpendicular to the thickness direction of the gluing layer, the air permeability deviation of the gluing layer is not greater than 2s / 100ml. The gluing layer provided by the invention has low air permeability, and the overall air permeability of the coating is uniform, so that the lithium ion transmission efficiency and the capacity retention rate of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of urban rail transit, and specifically relates to a coating layer and a preparation method thereof, a diaphragm, an electrode, a lithium ion battery and a preparation method thereof, and electrical equipment. Background Art

[0002] In recent years, lithium-ion batteries have been widely used in portable electronic devices, energy storage and electric vehicles due to their long cycle life, low cost, light weight and high capacity. Especially with the rapid development of the new energy industry, lithium batteries are increasingly used in electric vehicles. The market's requirements for lithium battery performance and safety have placed higher demands on the performance of the diaphragm, such as battery interface bonding problems, which seriously affect battery performance.

[0003] To improve the above problems, the current main solution is to coat a water-based PVDF adhesive layer on one or both sides of the polyolefin diaphragm. This coating layer can effectively improve the adhesion of the diaphragm, which greatly improves the process uniformity and interface adhesion of the battery. However, there are many problems in the existing water-based PVDF coating technology. The existing water-based PVDF coating has a large air permeability increment and uneven coating permeability, which affects the battery's capacity retention rate and ion transmission rate. Summary of the invention

[0004] In response to the technical problems in the prior art, the present application provides a coating layer and a preparation method thereof, a diaphragm, an electrode, a lithium-ion battery and a preparation method thereof, and electrical equipment.

[0005] In order to solve the above problems, this application provides the following solutions:

[0006] In a first aspect, the present application provides a coating layer, wherein the coating layer has pores and an air permeability of 10s / 100ml to 35s / 100ml; on a plane perpendicular to the thickness direction of the coating layer, the air permeability deviation of the coating layer is no more than 2s / 100ml.

[0007] In some embodiments, on a plane parallel to the thickness direction of the coating layer, the pore coverage is 20% to 65%.

[0008] In some preferred embodiments, the pore coverage is 40% to 65%.

[0009] In some embodiments, the average pore diameter of the pores is 10 nm to 5 um.

[0010] In some preferred embodiments, the average pore diameter of the pores is 10 nm to 70 nm.

[0011] In some embodiments, the pores are formed by dissolving organic matter that can be dissolved in the electrolyte.

[0012] In some embodiments, the coating layer also includes a rubber powder, and the rubber powder includes at least one of polyvinylidene fluoride (PVDF), polyethylene (PE) microspheres, polypropylene (PP) microspheres, polyacrylate (PMMA) microspheres, polyacrylonitrile (PAN) microspheres, and thermoplastic polyimide (TPI) microspheres.

[0013] In some embodiments, the particle size D50 of the colloid powder is 1 um to 6 um.

[0014] In some embodiments, the coating layer further includes a dispersant and a binder;

[0015] In some preferred embodiments, the dispersant includes an aliphatic amide dispersant, and the aliphatic amide dispersant includes one or more of polyacrylamide, ethylene glycol, triglyceride, polyvinyl alcohol, and lauric acid ester; and / or the binder includes a polyacrylic acid binder, and the polyacrylic acid binder includes one or more of polypropylene methyl ester, polyacrylate, polyacrylic acid-acrylonitrile copolymer, and polyacrylamide copolymer.

[0016] In a second aspect, the present application provides a method for preparing a coating layer, the preparation method comprising the following steps:

[0017] S1: Mixing the coating material and the organic matter to form a slurry;

[0018] S2: subjecting the slurry to a molding process, and removing organic matter from the material after the molding process to obtain the coating layer;

[0019] The coating layer is used in a battery. The battery includes an electrolyte, and the organic matter is soluble in the electrolyte.

[0020] In some embodiments, in step S1, the coating layer material includes a dispersant, a binder and a rubber powder, and the rubber powder includes at least one of polyvinylidene fluoride (PVDF), polyethylene (PE) microspheres, polypropylene (PP) microspheres, polyacrylate (PMMA) microspheres, polyacrylonitrile (PAN) microspheres, and thermoplastic polyimide (TPI) microspheres.

[0021] In some embodiments, the weight ratio of the dispersant, the colloid powder, the organic matter, and the binder is (0.5-2):(10-30):(1-30):(1-5).

[0022] In some embodiments, in step S1, the mixing process includes a stirring process, the stirring process time is 10 min to 2 h; the stirring process speed is 100 rpm to 400 rpm.

[0023] In some embodiments, in step S2, the molding process includes a drying process; and the removing of organic matter from the material after the molding process includes infiltrating the material after the molding process with an electrolyte.

[0024] In some embodiments, the melting point of the organic matter is 80°C to 95°C.

[0025] In some embodiments, the organic matter includes a plurality of organic particles, and the D50 of the plurality of organic particles is 10 nm to 5 um;

[0026] In some preferred embodiments, D50 of the plurality of organic particles is 10 nm to 70 nm.

[0027] In some embodiments, the organic matter includes at least one of an organic ester, an acid anhydride and an ether substance; the organic ester includes at least one of p-toluenesulfonyl isocyanate, propylene sulfate, diphenyl carbonate, propylene sultone, propylene-1,3 sultone, triphenyl phosphate, triphenyl phosphite and cyclopentane sulfone; the acid anhydride includes 2-(acetoxy)benzoic anhydride.

[0028] In a third aspect, the present application provides a diaphragm, comprising a base film and the adhesive layer described in the first aspect, or a adhesive layer prepared by the method for preparing the adhesive layer described in the second aspect, wherein the adhesive layer is arranged on the base film.

[0029] In a fourth aspect, the present application provides an electrode, comprising the coating layer described in the first aspect, or a coating layer prepared by the coating layer preparation method described in the second aspect, and the electrode is a positive electrode or a negative electrode.

[0030] In a fifth aspect, the present application provides a lithium-ion battery, comprising the separator described in the third aspect, and / or the electrode described in the fourth aspect.

[0031] In a sixth aspect, the present application provides a method for preparing a lithium ion battery, the preparation method comprising the following steps:

[0032] S1: Mixing the coating material and the organic matter to form a slurry;

[0033] S2: coating the slurry on at least one surface of the positive electrode, the separator, and the negative electrode.

[0034] S3: stacking the positive electrode, the separator and the negative electrode in sequence to obtain a lithium-ion battery core;

[0035] S4: injecting electrolyte into the lithium ion battery core to obtain a lithium ion battery;

[0036] The organic matter can be dissolved in the electrolyte.

[0037] In a seventh aspect, an electrical device is provided, comprising the lithium-ion battery described in the fifth aspect, and / or a lithium-ion battery prepared by the method for preparing a lithium-ion battery described in the sixth aspect.

[0038] The technical solution provided by the present application has the following technical effects: (1) The adhesive layer can be coated on the diaphragm or the electrode, and the coating method is simple and convenient to operate and has strong applicability; (2) The coating of the adhesive layer increases the insulation, can resist foreign matter such as metal burrs, and improves the breakdown voltage; (3) The air permeability of the adhesive layer is 10s / 100ml to 35s / 100ml, and the air permeability deviation of the adhesive layer on the plane perpendicular to the thickness direction of the adhesive layer is not more than 2s / 100ml; the adhesive layer provided by the present application has low air permeability and small air permeability deviation, which improves the capacity retention rate of the battery, improves the lithium ion transmission efficiency, and improves the battery performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0040] The structures, proportions, sizes, etc. illustrated in the drawings of this specification are only used to match the contents disclosed in the specification so as to facilitate understanding and reading by persons familiar with this technology. They are not used to limit the conditions under which the present invention can be implemented, and therefore have no substantive technical significance. Any structural modification, change in proportion or adjustment of size, without affecting the effects and purposes that can be achieved by the present invention, should still fall within the scope of the technical contents disclosed by the present invention.

[0041] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0042] Figure 1 is a schematic diagram of the diaphragm structure in some embodiments of the present invention;

[0043] Figure 2 It is a schematic diagram of the pole piece structure in some embodiments of the present invention.

[0044] Explanation of the reference numerals: A: pore; B: colloid powder; C: base film; D: pole piece. DETAILED DESCRIPTION

[0045] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0046] The invention provides a coating layer, which has pores and an air permeability of 10s / 100ml to 35s / 100ml; on a plane perpendicular to the thickness direction of the coating layer, the air permeability deviation of the coating layer is no more than 2s / 100ml.

[0047] Specifically, the air permeability of the coating layer can be, but is not limited to, 10s / 100ml, 15s / 100ml, 20s / 100ml, 25s / 100ml, 30s / 100ml, and 35s / 100ml; the air permeability of the coating layer reflects the permeability of the coating layer in the thickness direction. The smaller the air permeability of the coating layer, the greater the permeability, and the faster the lithium ions pass through the coating layer; on the contrary, the greater the air permeability of the coating layer, the smaller the permeability, and the slower the lithium ions pass through the coating layer; reducing the air permeability of the coating layer can improve the performance of the battery and improve the capacity retention rate of the battery. Among them, the test method of air permeability can refer to the test method of air permeability in GB / T 36363-2018 "Polyolefin separator for lithium ion batteries".

[0048] Specifically, on the plane perpendicular to the thickness direction of the rubber coating layer, the air permeability deviation of the rubber coating layer is no more than 2s / 100ml, which means that when the air permeability of the rubber coating layer is tested by the above-mentioned test method for the air permeability of the rubber coating layer at any two parts on the plane perpendicular to the thickness direction of the rubber coating layer, the difference in their air permeability is no more than 2s / 100ml, and the plane can be either a surface or a cross-section; the air permeability deviation of the rubber coating layer is no more than 2s / 100ml, which means that the air permeability deviations of each part on the plane perpendicular to the thickness direction of the rubber coating layer are small, and the pores in the rubber coating layer are evenly distributed.

[0049] In the present application, "s / 100 ml" means "seconds / 100 ml".

[0050] The coating layer provided in the present application has the following effects: (1) the coating layer can be coated on a diaphragm or an electrode, and the coating method is simple and convenient to operate and has strong applicability; (2) coating the coating layer increases insulation, can resist foreign matter such as metal burrs, and improves breakdown voltage; (3) the air permeability of the coating layer is 10s / 100ml to 35s / 100ml, and the air permeability deviation of the coating layer on a plane perpendicular to the thickness direction of the coating layer is not more than 2s / 100ml; the coating layer provided in the present application has low air permeability and small air permeability deviation, which improves the capacity retention rate of the battery, improves the lithium ion transmission efficiency, and improves the battery performance.

[0051] In some embodiments, on a plane parallel to the thickness direction of the coating layer, the pore coverage is 20% to 65%.

[0052] Specifically, on a plane parallel to the thickness direction of the coating layer, a pore coverage of 20% to 65% means that the pore area accounts for 20% to 65% of the plane area of ​​the coating layer. Specifically, it can be but not limited to 20%, 30%, 40%, 50%, 60%, 65%; the pore coverage describes the volume of the pores in the coating layer. The greater the pore coverage, the greater the pore volume in the coating layer, the stronger the permeability of the coating layer, and the faster the speed of lithium ions passing through the coating layer.

[0053] In some preferred embodiments, the pore coverage is 40% to 65%. When the pore coverage is within this range, the performance of the battery can be better improved and the capacity retention rate of the battery can be increased.

[0054] In some embodiments, the average pore size of the pores is 10 nm to 5 um.

[0055] Specifically, the average pore size can be, but is not limited to, 10nm, 100nm, 200nm, 500nm, 800nm, 1um, 3um, and 5um; the pore size represents the size of the organic matter. The larger the pore size, the smaller the air permeability of the coating layer and the faster the lithium ion transmission rate; the smaller the pore size, the better the mechanical strength of the coating layer and the less likely it is to cause powder falling. Therefore, when the pore size is within this range, the mechanical strength of the coating layer can be improved while improving the lithium ion transmission rate.

[0056] In some preferred embodiments, the average pore diameter of the pores is 10 nm to 70 nm.

[0057] Specifically, the average pore size of the pores can be but is not limited to 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, and 70nm; the average pore size of the pores is between 10nm and 70nm, which can better control the uniformity of the pores and improve the lithium ion transmission rate.

[0058] Specifically, the pore size can be obtained by the following test method: using N 2 Physical adsorption instrument was used to test the pore size, and the specific N 2 The physical adsorption data were analyzed on an Autosorbiq-XR instrument from Quantachrome Instruments, Inc., USA. 2 As the balance gas, H 2 As protective gas, the test temperature was -196 ° C. Sample pretreatment conditions were: programmed temperature rise to 200 ° C, duration of 12 h. The pore size distribution was obtained by the BaiTett-Joyner-Halenda method using the desorption branch.

[0059] In some embodiments, the pores are formed by dissolving organic matter that can be dissolved in the electrolyte.

[0060] Specifically, the pores are formed by the dissolution of organic matter soluble in the electrolyte, which means that in the process of making the coating layer, organic matter particles soluble in the electrolyte are added and mixed to obtain a coating layer slurry, the coating layer slurry is applied and dried to obtain the coating layer, and after the battery cell containing the coating layer is injected with liquid, the organic matter is dissolved in the electrolyte, thereby realizing the pores in the coating layer; and the pore coverage of the coating layer can be controlled by adjusting the proportion of the organic matter in the coating layer.

[0061] Specifically, the electrolyte refers to the electrolyte commonly used in lithium-ion batteries, and the solvent of the electrolyte can be selected from one or more of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate and ethylene carbonate.

[0062] In some embodiments, the coating layer also includes a rubber powder, and the rubber powder includes at least one of polyvinylidene fluoride (PVDF), polyethylene (PE) microspheres, polypropylene (PP) microspheres, polyacrylate (PMMA) microspheres, polyacrylonitrile (PAN) microspheres, and thermoplastic polyimide (TPI) microspheres.

[0063] Specifically, the glue powder exists in a solid form and plays a bonding role. The direct contact bonding of the glue powder can ensure the adhesion of the glue layer and make the glue layer less likely to fall off. In addition, the glue powder can also absorb and store part of the electrolyte, thereby improving the electrolyte wetting performance of the glue layer and further improving the transmission rate of lithium ions.

[0064] In some embodiments, the particle size D50 of the colloid powder is 1 um to 6 um.

[0065] Specifically, the particle size of the rubber powder can be but is not limited to 1um, 2um, 3um, 4um, 5um, and 6um; the particle size of the rubber powder is in the range of 1um to 6um, which can enhance the bonding strength between the rubber powder particles and control the size of the pores in the coating layer.

[0066] In some embodiments, the coating layer further includes a dispersant and a binder;

[0067] In some preferred embodiments, the dispersant includes an aliphatic amide dispersant, and the aliphatic amide dispersant includes one or more of polyacrylamide, ethylene glycol, triglyceride, polyvinyl alcohol, and lauric acid ester; and / or the binder includes a polyacrylic acid binder, and the polyacrylic acid includes one or more of polypropylene methyl ester, polyacrylate, polyacrylic acid-acrylonitrile copolymer, and polyacrylamide copolymer.

[0068] Specifically, the dispersant can evenly disperse the substances in the coating layer, ensuring that the organic matter is evenly distributed in the coating layer, facilitating the subsequent formation of uniform pore distribution; the binder can enhance the adhesion between particles and further improve the bonding strength of the coating layer.

[0069] In a second aspect, the present application provides a method for preparing the above-mentioned adhesive coating layer, comprising the following steps:

[0070] S1: Mixing the coating material and the organic matter to form a slurry;

[0071] S2: subjecting the slurry to a molding process, and removing organic matter from the material after the molding process to obtain a coating layer;

[0072] The coating layer is used in a battery. The battery includes an electrolyte, and the organic matter is soluble in the electrolyte.

[0073] Specifically, the molding process is to process the slurry into a solid form.

[0074] In some embodiments, in step S1, the coating layer material includes a dispersant, a binder and a rubber powder, and the rubber powder includes at least one of polyvinylidene fluoride (PVDF), polyethylene (PE) microspheres, polypropylene (PP) microspheres, polyacrylate (PMMA) microspheres, polyacrylonitrile (PAN) microspheres, and thermoplastic polyimide (TPI) microspheres.

[0075] In some embodiments, the weight ratio of the dispersant, colloid powder, organic matter, and binder is (0.5-2):(10-30):(1-30):(1-5).

[0076] Specifically, the weight ratio of the dispersant, the colloid powder, the organic matter and the binder is (0.5-2): (10-30): (1-30): (1-5), which can be but not limited to 0.5:15:30:2, 0.5:15:30:3, 1:20:15:5, 2:10:20:1; when the weight ratio of the dispersant, the colloid powder, the organic matter and the binder is within the above range, the formed coating layer has uniform pore distribution, low air permeability and good adhesion.

[0077] In some embodiments, in step S1, the mixing process includes a stirring process, and the stirring process time is 10 minutes to 2 hours; the stirring process speed is 100 rpm to 400 rpm.

[0078] Specifically, in step S1, the stirring time may be, but not limited to, 10 min, 30 min, 50 min, 1 h, 1.5 h, 2 h; the stirring speed may be, but not limited to, 100 rpm, 150 rpm, 200 rpm, 250 rpm, 300 rpm, 350 rpm, 400 rpm. When the stirring time and speed are within the above ranges, the substances in the slurry can be better mixed and uniformly mixed.

[0079] In some embodiments, in step S2, the molding process includes a drying process; and the removing of organic matter from the material after the molding process includes infiltrating the material after the molding process with an electrolyte.

[0080] Specifically, the molding process is to apply the coating layer slurry to the diaphragm or the electrode and perform a drying process; removing the organic matter in the material after the molding process includes infiltrating the coating layer containing organic matter with an electrolyte, and the organic matter dissolves in the electrolyte to form pores in the coating layer.

[0081] In some embodiments, the melting point of the organic matter is 80°C to 95°C.

[0082] Specifically, the melting point of the organic matter can be but is not limited to 80°C, 82°C, 85°C, 88°C, 90°C, 92°C, and 95°C; the melting point of the organic matter is within this range, which can ensure that the organic matter is not easy to volatilize and decompose during the coating process of the adhesive layer.

[0083] In some embodiments, the organic matter of the organic matter includes a plurality of organic matter particles, and D50 of the plurality of organic matter particles is 10 nm to 5 um; preferably, D50 of the plurality of organic matter particles is 10 nm to 70 nm.

[0084] Specifically, the size of the organic matter affects the pore size. The larger the pore size of the organic matter, the smaller the air permeability of the coating layer and the faster the lithium ion transmission rate. The smaller the pore size of the organic matter, the better the mechanical strength of the coating layer and the less likely it is to fall off. Therefore, when the pore size of the organic matter is within this range, it can better improve the mechanical strength of the coating layer while improving the lithium ion transmission rate.

[0085] In some embodiments, the organic matter includes at least one of an organic ester, an acid anhydride and an ether; the organic ester includes at least one of p-toluenesulfonyl isocyanate, propylene sulfate, diphenyl carbonate, propylene sultone, propylene-1,3 sultone, triphenyl phosphate, triphenyl phosphite and cyclopentane sulfone; the acid anhydride includes 2-(acetoxy)benzoic anhydride.

[0086] Specifically, the organic substances mentioned above can all be dissolved in the electrolyte and have stable properties. They are not easy to volatilize and decompose during the coating process of the adhesive layer, and can be dissolved in the electrolyte after the electrolyte is injected into the battery cell.

[0087] Compared with the prior art, the adhesive layer provided in the present application has a simple preparation method, is easy to operate, has strong applicability, and is easy to mass produce.

[0088] In a third aspect, the present application provides a diaphragm, comprising a base film and the adhesive layer described in the first aspect, or the adhesive layer prepared by the method for preparing the adhesive layer described in the second aspect, wherein the adhesive layer is disposed on the base film.

[0089] Specifically, there is no particular limitation on the separator, and the separator can be selected from separators conventionally used in battery systems, and the separator can be various types of separators such as PP and PE.

[0090] In a fourth aspect, the present application provides an electrode, comprising the coating layer described in the first aspect, or a coating layer prepared by the coating layer preparation method described in the second aspect, wherein the electrode comprises a positive electrode or a negative electrode.

[0091] In a fifth aspect, the present application provides a lithium-ion battery, comprising the separator described in the third aspect, and / or the electrode described in the fourth aspect.

[0092] In a sixth aspect, the present application provides a method for preparing a lithium ion battery, the preparation method comprising the following steps:

[0093] S1: Mixing the coating slurry and the organic matter to form a slurry;

[0094] S2: coating the slurry on at least one surface of the positive electrode, the separator, and the negative electrode;

[0095] S3: stacking the positive electrode, the separator and the negative electrode in sequence to obtain a lithium-ion battery core;

[0096] S4: injecting electrolyte into the lithium ion battery core to obtain a lithium ion battery;

[0097] The organic matter can be dissolved in the electrolyte.

[0098] Specifically, during the process of injecting liquid into the battery core, the organic matter in the coating layer is dissolved in the electrolyte to form the pores.

[0099] In a seventh aspect, an electrical device is provided, comprising the lithium-ion battery described in the fifth aspect, and / or a lithium-ion battery prepared by the method for preparing a lithium-ion battery described in the sixth aspect.

[0100] Specifically, the electrical equipment may include but is not limited to electric vehicles, mobile phones, tablet computers, laptop computers, wearable devices (watches, bracelets), digital cameras, etc.

[0101] The present invention is further described in detail below by way of examples.

[0102] Example 1

[0103] This embodiment is used to illustrate the adhesive layer and its preparation method, the diaphragm, the electrode, the lithium ion battery and its preparation method disclosed in the present invention, and includes the following steps:

[0104] (1) Preparation of the coating layer: The ratio of the adhesive powder (specifically PE microspheres with a particle size D50 of 2 um), organic particles (specifically propylene sulfate), dispersant (ammonium polyacrylate), and binder (polymethyl acrylate) is 15:30:0.5:2; ultrapure water is added to a stirring tank, and the dispersant, adhesive powder, and organic powder are added in sequence, pre-stirred for 2 hours at a stirring rate of 100 rpm; the binder is added and stirring is continued for 30 minutes at a stirring rate of 350 rpm.

[0105] The prepared slurry is evenly coated on a diaphragm (specifically a polyolefin diaphragm) by roller coating, and after drying, rolled up for standby use, thereby obtaining the desired diaphragm.

[0106] (2) Preparation of lithium-ion batteries: The positive electrode, separator, and negative electrode are stacked in sequence, shaped and hot-pressed, and then loaded into the battery aluminum shell. The battery cell is sent to an oven to dry excess moisture in the battery cell, and an appropriate amount of electrolyte is injected. The battery cell is then soaked, formed, aged, and divided in sequence to complete the battery process steps. The average pore size of the pores in the coating layer is 15 nm.

[0107] The resulting battery can be subjected to other battery tests.

[0108] Example 2

[0109] The difference between Example 2 and Example 1 is that the preparation of the adhesive layer is different, as follows, and the rest is the same as Example 1.

[0110] (1) Preparation of the coating layer: The ratio of the adhesive powder (specifically PVDF, particle size D50 is 2 um), organic particles (specifically propylene sulfone), dispersant (ethylene glycol), and binder (polymethyl acrylate) is 15:30:0.5:3; ultrapure water is added to a stirring tank, and the dispersant, adhesive powder and organic powder are added in sequence, pre-stirred for 2 hours at a stirring rate of 100 rpm; the binder is added and stirring is continued for 30 minutes at a stirring rate of 350 rpm.

[0111] The prepared slurry is evenly coated on a diaphragm (specifically a polyolefin diaphragm) by roller coating, and after drying, rolled up for standby use, thereby obtaining the desired diaphragm.

[0112] (2) Preparation of lithium-ion batteries: The positive electrode, separator, and negative electrode are stacked in sequence, shaped and hot-pressed, and then loaded into the battery aluminum shell. The battery cell is sent to an oven to dry excess moisture in the battery cell, and an appropriate amount of electrolyte is injected. The battery cell is then soaked, formed, aged, and divided in sequence to complete the battery process steps. The average pore size of the pores in the coating layer is 15 nm.

[0113] Example 3

[0114] The difference between Example 3 and Example 1 is that the preparation of the adhesive layer is different, as follows, and the rest is the same as Example 1.

[0115] (1) Preparation of the coating layer: The ratio of the adhesive powder (specifically PVDF, particle size D50 is 2 um), organic particles (specifically dimethyl carbonate), dispersant (triglyceride), and binder (polyacrylate) is 15:30:0.5:3; ultrapure water is added to a stirring tank, and the dispersant, adhesive powder and organic powder are added in sequence, pre-stirred for 2 hours at a stirring rate of 100 rpm; the binder is added and stirring is continued for 30 minutes at a stirring rate of 350 rpm.

[0116] The prepared slurry is evenly coated on a diaphragm (specifically a polyolefin diaphragm) by roller coating, and after drying, rolled up for standby use, thereby obtaining the desired diaphragm.

[0117] (2) Preparation of lithium-ion batteries: The positive electrode, separator, and negative electrode are stacked in sequence, shaped and hot-pressed, and then loaded into the battery aluminum shell. The battery cell is sent to an oven to dry excess moisture in the battery cell, and an appropriate amount of electrolyte is injected. The battery cell is then soaked, formed, aged, and divided in sequence to complete the battery process steps. The average pore size of the pores in the coating layer is 15 nm.

[0118] Example 4

[0119] The difference between Example 4 and Example 1 is that the preparation of the adhesive layer is different, as follows, and the rest is the same as Example 1.

[0120] (1) Preparation of the coating layer: The ratio of the adhesive powder (specifically PVDF, particle size D50 is 2 um), organic particles (diethyl carbonate), dispersant (polyvinyl alcohol), and adhesive (polyacrylic acid-acrylonitrile copolymer) is 15:30:0.5:3; ultrapure water is added to a stirring tank, and the dispersant, adhesive powder, and organic powder are added in sequence, pre-stirred for 2 hours at a stirring rate of 100 rpm; the adhesive is added and stirring is continued for 30 minutes at a stirring rate of 350 rpm.

[0121] The prepared slurry is evenly coated on a diaphragm (specifically a polyolefin diaphragm) by roller coating, and after drying, rolled up for standby use, thereby obtaining the desired diaphragm.

[0122] (2) Preparation of lithium-ion batteries: The positive electrode, separator, and negative electrode are stacked in sequence, shaped and hot-pressed, and then loaded into the battery aluminum shell. The battery cell is sent to an oven to dry excess moisture in the battery cell, and an appropriate amount of electrolyte is injected. The battery cell is then soaked, formed, aged, and divided in sequence to complete the battery process steps. The average pore size of the pores in the coating layer is 15 nm.

[0123] Example 5

[0124] The difference between Example 5 and Example 1 is that the preparation of the adhesive layer is different, as follows, and the rest is the same as Example 1.

[0125] (1) Preparation of the coating layer: The ratio of the adhesive powder (specifically PVDF, particle size D50 is 2 um), organic particles (triphenyl phosphate), dispersant (lauric acid ester), and adhesive (polyacrylamide copolymer) is 15:30:0.5:3; add ultrapure water to a stirring tank, and then add the dispersant, adhesive powder, and organic powder in sequence, pre-stir for 2 hours at a stirring rate of 100 rpm; add the adhesive and continue stirring for 30 minutes at a stirring rate of 350 rpm.

[0126] The prepared slurry is evenly coated on a diaphragm (specifically a polyolefin diaphragm) by roller coating, and after drying, rolled up for standby use, thereby obtaining the desired diaphragm.

[0127] (2) Preparation of lithium-ion batteries: The positive electrode, separator, and negative electrode are stacked in sequence, shaped and hot-pressed, and then loaded into the battery aluminum shell. The battery cell is sent to an oven to dry excess moisture in the battery cell, and an appropriate amount of electrolyte is injected. The battery cell is then soaked, formed, aged, and divided in sequence to complete the battery process steps. The average pore size of the pores in the coating layer is 15 nm.

[0128] Comparative Example 1

[0129] The difference between Comparative Example 1 and Example 1 is that there is no glue coating layer, and the rest is the same as Example 1.

[0130] Comparative Example 2

[0131] The difference between Comparative Example 2 and Example 1 is that the preparation of the adhesive layer is different, and the rest is the same as Example 1.

[0132] (1) Preparation of the coating layer: The ratio of the adhesive powder (specifically PVDF, with a particle size D50 of 2 μm), the dispersant (specifically polyacrylate), the binder (specifically polyacrylonitrile-polyacrylate copolymer), and the wetting agent (specifically siloxane) is 90:4:5:1; ultrapure water is added to a stirring tank, and then the dispersant and the adhesive powder are added in sequence, and pre-stirred for 2 h at a stirring rate of 300 rpm; the binder is added and stirring is continued for 30 min at a stirring rate of 350 rpm.

[0133] The prepared slurry is evenly coated on a diaphragm (specifically a polyolefin diaphragm) by roller coating, and after drying, rolled up for standby use, thereby obtaining the desired diaphragm.

[0134] Comparative Example 3

[0135] The difference between Comparative Example 3 and Example 1 is that the preparation of the adhesive layer is different, and the rest is the same as Example 1.

[0136] (1) Preparation of the coating layer: The ratio of the adhesive powder (specifically PVDF, with a particle size D50 of 2 μm), the dispersant (specifically polyacrylate), the binder (specifically polyacrylonitrile-polyacrylic acid copolymer), and the wetting agent (specifically acetylene glycol) is 90:3:5:2; ultrapure water is added to a stirring tank, and then the dispersant and the adhesive powder are added in sequence, and pre-stirred for 2 h at a stirring rate of 200 rpm; the binder is added and stirring is continued for 30 min at a stirring rate of 350 rpm.

[0137] The prepared slurry is evenly coated on the diaphragm (specifically a polyolefin diaphragm) by rotary spraying, and the coating amount is 0.6 g / m 2 After drying, the film is rolled up for later use to obtain the desired diaphragm.

[0138] Test method:

[0139] (1) Air permeability: Refer to the air permeability test method in GB / T 36363-2018 "Polyolefin separators for lithium-ion batteries".

[0140] (2) Porosity coverage: The cross section of the coating is photographed using a Keyence microscope, and the area ratio of the pores to the field of view is calculated using software, which is the pore coverage.

[0141] (3) Ionic conductivity: Refer to the test method for ionic conductivity in GB / T 36363-2018 “Polyolefin separators for lithium-ion batteries”.

[0142] (4) Electrochemical performance test: The battery was charged at a constant current of 1C to 3.8V and left for 30 min; then discharged at a current of 1C to a discharge termination voltage of 2.0V and left for 30 min; the above two steps were repeated 300 times in total, and the first discharge capacity was recorded as the battery discharge capacity C1, and the discharge capacity of the 300th cycle was recorded as C300; 300-cycle capacity retention rate % = (C300 / C1)*100%.

[0143] Table 1 Performance test results of various embodiments and comparative examples

[0144]

[0145] In summary, it can be seen from the data of Examples 1 to 5 and Comparative Examples 1 to 3 that the air permeability of the coating layer is 10s / 100ml to 35s / 100ml, and the coating air permeability deviation is no more than 2s / 100ml, which can improve the capacity retention rate of the battery, improve the ionic conductivity, and effectively improve the battery performance. The coating layer provided in the present application can be coated on the diaphragm or the electrode, and the coating method is simple and convenient to operate, has strong applicability, and can resist foreign matter such as metal burrs.

[0146] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A coating layer, characterized in that: The rubber coating layer has pores, and the air permeability of the rubber coating layer is 10s / 100ml to 35s / 100ml. On a plane perpendicular to the thickness direction of the rubber coating layer, the air permeability deviation of the rubber coating layer is no more than 2s / 100ml.

2. The adhesive coating according to claim 1, characterized in that: On a plane parallel to the thickness direction of the adhesive layer, the pore coverage is 20% to 65%.

3. The adhesive coating layer according to claim 1, characterized in that: The pore coverage is 40% to 65%.

4. The adhesive coating layer according to claim 1, characterized in that: The average pore size of the pores is 10 nm to 5 um; preferably, the average pore size of the pores is 10 nm to 70 nm.

5. The adhesive coating layer according to claim 1, characterized in that: The pores are formed by dissolving organic matter that can be dissolved in the electrolyte.

6. The adhesive coating layer according to claim 1, characterized in that: The coating layer includes a rubber powder, and the rubber powder includes at least one of polyvinylidene fluoride (PVDF), polyethylene (PE) microspheres, polypropylene (PP) microspheres, polyacrylate (PMMA) microspheres, polyacrylonitrile (PAN) microspheres, and thermoplastic polyimide (TPI) microspheres.

7. The adhesive coating layer according to claim 6, characterized in that: The particle size D50 of the rubber powder is 1 um to 6 um.

8. The adhesive coating layer according to claim 6, characterized in that: The coating layer also includes a dispersant and a binder; Preferably, the dispersant comprises an aliphatic amide dispersant, and the aliphatic amide dispersant comprises one or more of polyacrylamide, ethylene glycol, triglyceride, polyvinyl alcohol, and lauric acid ester; and / or The binder includes a polyacrylic binder, and the polyacrylic binder includes one or more of polypropylene methyl ester, polyacrylate, polyacrylic acid-acrylonitrile copolymer, and polyacrylamide copolymer.

9. A method for preparing a rubber coating layer, characterized in that: The preparation method comprises the following steps: S1: Mixing the coating material and the organic matter to form a slurry; S2: subjecting the slurry to a molding process, and removing organic matter from the material after the molding process to obtain a coating layer; the coating layer is used for a battery, the battery includes an electrolyte, and the organic matter is soluble in the electrolyte.

10. The method for preparing the adhesive layer according to claim 9, characterized in that: In step S1, the coating layer material includes a dispersant, a binder and a glue powder, and the glue powder includes at least one of polyvinylidene fluoride (PVDF), polyethylene (PE) microspheres, polypropylene (PP) microspheres, polyacrylate (PMMA) microspheres, polyacrylonitrile (PAN) microspheres, and thermoplastic polyimide (TPI) microspheres.

11. The method for preparing the adhesive layer according to claim 10, characterized in that: The weight ratio of the dispersant, the colloid powder, the organic matter and the binder is (0.5-2):(10-30):(1-30):(1-5).

12. The method for preparing a rubber coating layer according to any one of claims 9 to 11, characterized in that: In step S1, the mixing process includes a stirring process, the stirring process time is 10 minutes to 2 hours; the stirring process speed is 100 rpm to 400 rpm.

13. The method for preparing a rubber coating layer according to any one of claims 9 to 12, characterized in that: In step S2, the molding process includes a drying process; and the removing of organic matter from the material after the molding process includes infiltrating the material after the molding process with an electrolyte.

14. The method for preparing a rubber coating layer according to any one of claims 9 to 13, characterized in that: The melting point of the organic matter is 80°C to 95°C.

15. The method for preparing a rubber coating layer according to any one of claims 9 to 14, characterized in that: The organic matter includes a plurality of organic particles, and the D50 of the plurality of organic particles is 10nm-5um; preferably, the D50 of the plurality of organic particles is 10nm-70nm.

16. The method for preparing the adhesive layer according to claim 9, characterized in that: The organic matter includes at least one of organic esters, acid anhydrides and ether substances; the organic ester includes at least one of p-toluenesulfonyl isocyanate, propylene sulfate, diphenyl carbonate, propylene sultone, propylene-1,3 sultone, triphenyl phosphate, triphenyl phosphite and cyclopentane sulfone; the acid anhydride includes 2-(acetoxy)benzoic anhydride.

17. A diaphragm, characterized in that: The invention comprises a base film and the adhesive layer according to claims 1 to 8, or the adhesive layer prepared by the method for preparing the adhesive layer according to claims 9 to 16, wherein the adhesive layer is arranged on the base film.

18. An electrode, characterized in that: It comprises the coating layer described in claims 1 to 8, or the coating layer prepared by the method for preparing the coating layer described in claims 9 to 16; the electrode is a positive electrode or a negative electrode.

19. A lithium ion battery, characterized in that: Comprising the separator according to claim 17 and / or the electrode according to claim 18.

20. A method for preparing a lithium ion battery, characterized in that: The preparation method comprises the following steps: S1: Mixing the coating material and the organic matter to form a slurry; S2: coating the slurry on at least one surface of the positive electrode, the separator, and the negative electrode; S3: stacking the positive electrode, the separator and the negative electrode in sequence to obtain a lithium-ion battery core; S4: injecting electrolyte into the lithium ion battery core to obtain a lithium ion battery; The organic matter can be dissolved in the electrolyte.

21. An electrical equipment, characterized in that: Including the lithium ion battery according to claim 19, and / or a lithium ion battery prepared by the method for preparing a lithium ion battery according to claim 20.